2015
DOI: 10.1093/ejcts/ezu509
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment to UK cardiothoracic surgery in the era of public outcome reporting

Abstract: Repeated negative messages have had a detrimental influence on recruitment. Because 55% of UK medical graduates, but less than 5% of CT surgeons are female, recruitment problems may worsen. Action is needed to restore interest in the specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 12 publications
1
22
1
Order By: Relevance
“… 3 This is similar to the experience in the UK where recent studies revealed a decline in interest in CTS among UK graduates. 4 , 5 The entry point into a CTS programme in the West African sub-region is similar to that of the UK, where the application for entry is made at the level of PGY-2, unlike in the USA, where most cardiothoracic surgeons complete an initial general surgery training.…”
Section: Discussionmentioning
confidence: 99%
“… 3 This is similar to the experience in the UK where recent studies revealed a decline in interest in CTS among UK graduates. 4 , 5 The entry point into a CTS programme in the West African sub-region is similar to that of the UK, where the application for entry is made at the level of PGY-2, unlike in the USA, where most cardiothoracic surgeons complete an initial general surgery training.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, 2 cardiothoracic training pathways exist-a 6-year program after 2 years of core surgical training and, as of 2013, an 8-year specialty ''run-through'' program. 2 A move toward earlier specialization, as well as recent difficulties identified in trainee recruitment, 3 indicates a need for early exposure to not only stimulate interest and provide career insight, but to obtain experience necessary for an informed application to a competitive process.…”
Section: Cardiothoracic Surgery Exposure In Medical School--a United mentioning
confidence: 99%
“…When Donald Berwick was asked by the British prime minister to review the state of the NHS, he reiterated, "Hospitals, not individuals, must be held accountable for poor outcomes" [24,25]. Nevertheless, the process did reduce mortality to low levels in a system where most cardiac centers were not funded for circulatory support equipment and team consistency was poor through the European Working Time Directive.…”
Section: International Experiences With Public Reporting Of Cardiac Smentioning
confidence: 99%
“…There is broad agreement that the individually focused "name and shame" agenda has affected recruitment to cardiothoracic surgery in the United Kingdom. Currently, only 40% of pediatric cardiac surgeons, 54% of thoracic surgeons, and 64% of adult cardiac surgeons had their medical training in the United Kingdom [25]. From the General Medical Council Specialist Register, we know that 68% of trainees entering cardiothoracic surgery at the time of the Bristol children's heart scandal (2000) were UK graduates.…”
Section: International Experiences With Public Reporting Of Cardiac Smentioning
confidence: 99%